Child Labor in Brazil: the importance of public policies for its eradication - Vicente, Aparecido Renan; Alves, Nathaly Martinez; Leao, Andreza Marques de Castro [UNESP] (Univ Federal Santa Maria, 2025)
This article points out some considerations about child labor and public policies to eradicate it. It is based on qualitative research and consists of a bibliographical review. The selection of materials for this review was based on an initial reading of the titles and abstracts of works related to the theme of this article. It was possible to find studies aligned with its scope, which were examined in full so that they could be better understood. At the end of this process, only studies that specifically dialogue with the theme in question and were intrinsically related were included. It was possible to verify that poverty and low schooling are some of the main causes of child labor, together with ineffective public policies. Nevertheless, even after the enactment of the Statute of the Child and Adolescent, the main law that provides for the comprehensive protection of this population, and the creation of the Child Labor Eradication Program (PETI), statistics point to the challenge of properly eradicating this problem, which reveals that there is an urgent need for studies aimed at measuring this phenomenon from a preventive perspective, and the effectiveness of these policies, since child labor continues to be a serious social problem in Brazil.
Keywords: Keywords : Child Labor; Public Policies; Protection.